Population-Scale Polymorphic Short Tandem Repeat Provides an Alternative Strategy for Allele Mining in Cotton - Mei, Huan; Zhao, Ting; Dong, Zeyu; Han, Jin; Xu, Biyu; Chen, Rui; Zhang, Jun; Zhang, Juncheng; Hu, Yan; Zhang, Tianzhen; Fang, Lei (Frontiers in Plant Science, 2022)
Short tandem repeats (STRs), which vary in size due to featuring variable numbers of repeat units, are present throughout most eukaryotic genomes. To date, few population-scale studies identifying STRs have been reported for crops. Here, we constructed a high-density polymorphic STR map by investigating polymorphic STRs from 911 Gossypium hirsutum accessions. In total, we identified 556,426 polymorphic STRs with an average length of 21.1 bp, of which 69.08% were biallelic. Moreover, 7,718 (1.39%) were identified in the exons of 6,021 genes, which were significantly enriched in transcription, ribosome biogenesis, and signal transduction. Only 5.88% of those exonic STRs altered open reading frames, of which 97.16% were tri-nucleotide. An alternative strategy STR-GWAS analysis revealed that 824 STRs were significantly associated with agronomic traits, including 491 novel alleles that undetectable by previous SNP-GWAS methods. For instance, a novel polymorphic STR consisting of GAACCA repeats was identified in GH_D06G1697, with its (GAACCA)5 allele increasing fiber length by 1.96-4.83% relative to the (GAACCA)4 allele. The database CottonSTRDB was further developed to facilitate use of STR datasets in breeding programs. Our study provides functional roles for STRs in influencing complex traits, an alternative strategy STR-GWAS for allele mining, and a database serving the cotton community as a valuable resource.